A Case of Extrinsic Compression of the Left Main Coronary Artery Secondary to Pulmonary Artery Dilatation - Choi, Yoon-Jung; Kim, Ung; Lee, Jin-Sung; Park, Won-Jong; Lee, Sang-Hee; Park, Jong-Seon; Shin, Dong-Gu; Kim, Young-Jo (Journal of Korean medical science, 2013)
Extrinsic compression of the left main coronary artery (LMCA) secondary to pulmonary artery dilatation is a rare syndrome. Most cases of pulmonary artery hypertension but no atherosclerotic risk factors rarely undergo coronary angiography, and hence, diagnoses are seldom made and proper management is often delayed in these patients. We describe a patient that presented with pulmonary hypertension, clinical angina, and extrinsic compression of the LMCA by the pulmonary artery, who was treated successfully by percutaneous coronary intervention. Follow-up coronary angiography showed patent stent in the LMCA in the proximity of the dilated main pulmonary artery. This case reminds us that coronary angiography and percutaneous coronary intervention should be considered in pulmonary hypertension patients presenting with angina or left ventricular dysfunction.